2008
DOI: 10.1007/s00280-008-0745-3
|View full text |Cite
|
Sign up to set email alerts
|

Sodium selenite induces apoptosis by generation of superoxide via the mitochondrial-dependent pathway in human prostate cancer cells

Abstract: Purpose-Studies have demonstrated that selenium supplementation reduces the incidence of cancer, particularly prostate cancer. Evidence from experimental studies suggests that apoptosis is a key event in cancer chemoprevention by selenium and reactive oxygen species play a role in induction of apoptosis by selenium compounds. The current study was designed to investigate the role of superoxide and mitochondria in selenite-induced apoptosis in human prostate cancer cells.Methods-LNCaP cells were transduced with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
96
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(108 citation statements)
references
References 43 publications
12
96
0
Order By: Relevance
“…At the same time, MnTMPyP could inhibit cytochrome c release from mitochondria and the activation of caspase-9, -3 induced by 20 μM sodium selenite. Xiang et al also reported that the overexpression of MnSOD could suppress selenite-induced mitochondrial membrane potential decrease and meanwhile inhibit the release of cytochrome c from mitochondria to cytosol (19). Combined together, these results indicate that the alteration of subcellular localization of MnSOD is likely a primary effect of sodium selenite treatment and not a consequent event of apoptosis.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…At the same time, MnTMPyP could inhibit cytochrome c release from mitochondria and the activation of caspase-9, -3 induced by 20 μM sodium selenite. Xiang et al also reported that the overexpression of MnSOD could suppress selenite-induced mitochondrial membrane potential decrease and meanwhile inhibit the release of cytochrome c from mitochondria to cytosol (19). Combined together, these results indicate that the alteration of subcellular localization of MnSOD is likely a primary effect of sodium selenite treatment and not a consequent event of apoptosis.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have demonstrated that the superoxide production in mitochondria is a key event during selenite-induced apoptosis process (18)(19)(20)(21). However, the molecular mechanism of how sodium selenite triggers the accumulation of superoxide remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, neither melatonin nor silibinin are able to induce cell death which makes a difference in the outcome triggered by other antioxidants. 42,43 On the contrary, both antioxidants redirect cells toward a transdifferentiation process that matches a NE-like phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of evidence has recently demonstrated the protective role of selenium against several major types of cancers including gastric cancer (Liu and Russell 2008;Lee et al 2011). For example, several studies have reported that sodium selenite induces apoptosis in human osteosarcoma, prostate cancer and leukemia (Cao et al 2006;Xiang et al 2009;Chen et al 2012). However, the precise mechanism by which sodium selenite exerts an inhibitory effect on gastric cancer is unclear.…”
Section: Introductionmentioning
confidence: 99%